ANALISIS STUDI KELAYAKAN BISNIS PUDDING LAMOTA DITINJAU DARI ASPEK PEMASARAN DAN KEUANGAN - Elsa Rahmawati Patmawati (MANAJEMEN DEWANTARA, 2024)
Business or business feasibility studies are very suitable for various business categories including UMKM. Business or business feasibility studies have a very large role for the success and sustainability of micro, small and medium enterprises (UMKM). The profitable business scale resulting from business feasibility will have an impact on making the necessary policies or business strategies so that it will have an impact on the sustainability of the UMKM business. The data analysis technique applied in the research is non-financial analysis, namely the marketing aspect which is viewed from the marketing mix strategy (marketing mix strategy) including product, price, distribution and promotion. Data analysis in this research uses the Payback Period (PP) analysis technique. The formula for calculating the Payback Period (PP) formula is as follows. The results of the business feasibility analysis from the marketing aspect are said to be feasible, namely products that have an attractive brand name and create affordable packaging, have a strategic location and easy distribution and attractive promotions. Analysis of the feasibility of the business from the financial aspect resulted that the capital came from the capital owner and resulted in a payback period (PP) of  2 months 5 weeks.